PREPARATION, CHARACTERIZATION AND CATALYTIC ACTIVITY TEST OF CoMo/ZnO CATALYST ON ETHANOL CONVERSION USING STEAM REFORMING METHOD - Wega Trisunaryanti; Handirofa Handirofa; Triyono Triyono; Suryo Purwono (Indonesian Journal of Chemistry, 2009)
Preparation, characterization and catalytic activity test of CoMo/ZnO catalyst for steam reforming of ethanol have been investigated. The catalysts preparation was carried out by impregnation of Co and/or Mo onto ZnO sample. Water excess was used in ethanol feed for steam reforming process under mol ratio of ethanol:water (1:10). Characterizations of catalysts were conducted by analysis of metal content using Atomic Absorption Spectroscopy (AAS). Determination of catalysts acidity was conducted by gravimetric method of adsorption of pyridine base. Catalytic activity test on ethanol conversion using steam reforming method was conducted in a semi-flow reactor system, at a temperature of 400 oC, for 1.5 h under N2 flow rate of 10 mL/min. Gas product was analyzed by gas chromatograph with TCD system. The results of catalysts characterizations showed that the impregnation of Co and/or Mo metals on ZnO sample increased its acidity and specific surface area. The content of Co in Co/ZnO and CoMo/ZnO catalysts was 1.14 and 0.49 wt%. The Mo content in CoMo/ZnO catalyst was 0.36 wt%. The catalytic activity test result on ethanol conversion showed that the ZnO, Co/ZnO, and CoMo/ZnO catalysts produced gas fraction of 16.73, 28.53, and 35.53 wt%, respectively. The coke production of ZnO, Co/ZnO, and CoMo/ZnO catalysts was 0.86, 0.24, and 0.08 wt%, respectively. The gas products consisted mainly of hydrogen.